78 EXPRESSION LEVELS OF FMR-1 ISOFORMS IN MOUSE TESTIS. Issue 1 (1st January 2007) - Jorgensen, T.; Brackett, D.; Morris, D.
Abstract : Background: Fragile X syndrome is the number one cause of inherited mental retardation in humans. The syndrome results from the silencing of the Fmr1 gene, which codes for the fragile X mental retardation protein (FMRP). Previous studies have identified functional domains within FMRP, including 2 KH domains and an RGG box, which bind RNA, and a nuclear export signal (NES). FMRP has been proposed to play an important function in cells as it binds brain mRNA associated with polysomes. The gene is alternatively spliced into as many as 12 different mRNA transcripts. The majority of the functional domains of FMRP are affected by alternative splicing. These alterations in FMRP structure are expected to dramatically alter the biological properties of the isoforms. Fragile X syndrome displays the most significant phenotype in the brain and testis, characterized by severe macroorchadism in the latter. To more clearly understand this phenotype, the expression levels of the six major Fmr1 transcripts were determined in whole mouse testis. Study Design and Methods: To determine quantitative expression levels of the six major Fmr1 isoforms in testis samples, quantitative real-time PCR was used. Current studies under way in the Morris laboratory are using mouse as a model system to investigate the expression levels of Fmr1 in whole brain samples. They have done this by developing primers that target each of the 12 different Fmr1 isoforms separately. The data have suggested that only 6 of the 12 are expressed to a significant degree. Therefore, primers targeting these 6 isoforms were used to quantitatively characterize whole testis samples. To normalize the data obtained, a gene that has been shown to be uniformly expressed throughout the body, the mouse form of the human acidic ribosomal binding protein, was also quantized. This allowed normaliazation of the data so they may be compared with one another. Results: The isoform expression profile shows isoform 8 being expressed most abundantly, followed closely by 1. In descending order of abundance were isoforms 2, 3, 7, and 9. Seven and nine were present in very low quantities and essentially indistinguishable from one another. Conclusion: The testis show an isoform expression profile almost identical to that observed in the brain. Although the expression profile was similar, the absolute amounts were far lower than that observed in the brain. Future studies may look at which cells express Fmr1 in the testis to further illuminate the origins of macroorchadism in patients with fragile X syndrome.